Enteral Nutrition Tolerability Assessment in Septic Shock Patients in The ICU of RSUP H. Adam Malik Medan - Ansari, Aulia Kamal; Lubis, Andriamuri Primaputra; Nadeak, Rommy Fransiscus (Perhimpunan Dokter Spesialis Anestesiologi dan Terapi Intensif, 2024)
Background: Enteral nutrition is recommended within 24 to 48 hours after intensive care unit (ICU) admission when resuscitation and hemodynamic stability have been achieved. This study aims to determine the tolerability of enteral nutrition in septic shock patients in the ICU. Objective: To determine the tolerability of enteral nutrition in septic shock patients in the ICU of RSUP H. Adam Malik Medan.Methods: This study is a retrospective observational study, which was conducted in the ICU of the RSUP H. Adam Malik Medan by taking patient data from January to December 2022. The samples were septic shock patients who were admitted to the ICU using mechanical ventilation and vasopressors with a length of treatment of more than 48 hours. Data was collected on the time required for enteral nutrition administration, as well as assessing patient tolerability (presence of vomiting, residuals, and incidence of ileus). Other assessments included length of stay and mortality rate.Result: This study consisted of 47 samples, with 23 male (48.9%) and 24 female (51.1%) samples. Based on the underlying disease, 40.4% of the samples were diagnosed with pneumonia. In the tolerability of enteral nutrition, 83% of the samples were tolerant of early enteral nutrition, but with a high mortality rate of 89.4%. The initiation time of enteral nutrition in patients was 4.94 ± 1.79 hours (p=0.001). The average hospital stay for sepsis patients was 7.30 ± 6.55 days (p=0.001).Conclusion: Most sepsis and septic shock patients in the ICU are tolerant of early enteral nutrition <24 hours, but it does not reduce mortality.